PixelQuery: Efficient Distance Range Join Query Technique for Visualization Analysis - Bo Pang; Zebang Liu; Wei Xiong; Mengyu Ma (ISPRS International Journal of Geo-Information)
A distance range join query (DRJQ) is a fundamental and critical operation in spatial database queries. It identifies geographic elements within specified distance ranges. This technique has a wide range of applications in multiple domains, including Geographic Information Systems (GISs), urban planning, and environmental monitoring. However, performing a DRJQ on large-scale spatial data remains a challenging problem, as the computational complexity of existing techniques escalates rapidly with increasing volumes of data. We propose PixelQuery, an efficient DRJQ method specifically optimized for visualization analysis. PixelQuery integrates spatial indexing with visualization-oriented strategies. It directly computes the display values of query results within the viewport, substantially lowering computational costs. Experiments conducted on datasets of varying scales demonstrate that this method can handle visualization queries involving tens of millions of elements on a standard laptop, with a maximum processing time of only 7.64 s. This technology provides a robust solution for rapid DRJQ processing and the visualization of large-scale vector data, offering promising potential for a diverse range of applications.